(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1865)
A transcription of John Pollexfen’s presentation to the Numismatic Society of London on the coins found on the Isle of Bute in 1863. In his presentation, he provides a catalogue of the coins and analyses the quality and decoration of the collection. He also discusses the historical and numismatic significance of the coins found in Bute.